Immunogenicity of Local and Massachusetts Strains Infectious Bronchitis Virus - Rahmahani, Jola; Wudhu, R Zaksara Fero Ali Mutaqin; Suwarno, Suwarno; Tacharina, Martia Rani (Universitas Airlangga, 2022)
This study aimed to compare the immunogenicity between the whole virus and protein S of both local strain I-147 and Massachusetts strain of Infectious bronchitis virus with indirect ELISA. 24 healthy mice are divided into four groups with six mice in each group that are: P1) a group of mice that are vaccinated with S protein (spike glycoprotein) of local strain Infectious Bronchitis virus; P2) a group of mice that are vaccinated with S protein (spike glycoprotein) of Massachusetts strain Infectious Bronchitis virus; P3) a group of mice that are vaccinated with the whole virus of local strain Infectious Bronchitis virus; P4) a group of mice that are vaccinated with the whole virus of Massachusetts strain Infectious Bronchitis virus. The results of this research are Optical Density (OD) values of each treatment, then to be analyzed using One Way ANOVA and followed by Duncan Multiple Range Test 5% and T-test. The results show that there are differences in immunogenicity between the whole virus and S protein in both the local strain and Massachusetts strain of Infectious bronchitis virus. The OD value of the whole virus in the two strains has a significant difference from the OD value of the protein S antigen in both strains, both in the serum taken at week 2 and week 4 post-vaccination.